2020
DOI: 10.3386/w27333
|View full text |Cite
|
Sign up to set email alerts
|

Temperature, Disease, and Death in London: Analyzing Weekly Data for the Century from 1866-1965

Abstract: Using weekly mortality data for London spanning 1866-1965, we analyze the changing relationship between temperature and mortality as the city developed. Our results show that both warm and cold weeks were associated with elevated mortality in the late 19th-century, but heat effects, due mainly to infant deaths from digestive diseases, largely disappeared after WWI. The resulting change in the temperature-mortality relationship meant that thousands of heat-related deaths-equal to 0.8-1.3 percent of all deaths-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The 300,000 mortality observations in our main data (Hanlon, Hansen, and Kantor 2020) cover 4,540 weeks stretching from 1866 to 1965, with breaks in 1915-1918 (WWI) and 1940-1948 (WWII). We end our main study period in 1965 because the geographic area for which our data are reported changed at that point, though in Online Appendix A.2, we present supplementary results for 1981-2006.…”
Section: Datamentioning
confidence: 84%
“…The 300,000 mortality observations in our main data (Hanlon, Hansen, and Kantor 2020) cover 4,540 weeks stretching from 1866 to 1965, with breaks in 1915-1918 (WWI) and 1940-1948 (WWII). We end our main study period in 1965 because the geographic area for which our data are reported changed at that point, though in Online Appendix A.2, we present supplementary results for 1981-2006.…”
Section: Datamentioning
confidence: 84%
“…While the coefficients are smaller than those in table 5, with the impact of a one percentage point increase in CWS on waterborne disease mortality falling to closer to 0.2%, CWS retains its significance. 1871-1900 1871-1900 1871-1900 1871-1900 1871-1900 1882-1900 1882-1894 1876-1900 (Hanlon, Hansen and Kantor 2020). 25 Comparing columns 4 and 5 suggests expansion of CWS in other companies' districts slowed the increase in mortality during the drought years.…”
Section: Narrowing the Windowmentioning
confidence: 99%
“…It is estimated that a one‐percentage‐point increase in the population with access to a constant water supply caused as much as a 0.4 per cent reduction in mortality from waterborne disease. Among other articles on the topic of London was one by Hanlon et al., who analyse the effect of temperature on mortality in the capital city over the century from 1866 to 1965. Using weekly temperature data and weekly mortality data disaggregated by cause and age group, they arrive at a number of conclusions.…”
mentioning
confidence: 99%